AI-Powered Predictive Customer Lifetime Value: Maximizing Long-Term Profits - Egorenkov, Dmitrii (International Journal of Scientific Research and Management (IJSRM), 2024)
In an era where data-driven decision-making is critical to business success, understanding and optimizing Customer Lifetime Value (CLV) has become a strategic priority for companies across industries. CLV, which estimates the total revenue a business can expect from a customer throughout their relationship, is crucial for identifying high-value customers and tailoring marketing strategies to maximize profitability. However, traditional methods of calculating CLV often rely on historical data and linear models, limiting their accuracy and adaptability in a rapidly changing market environment. The integration of Artificial Intelligence (AI) into predictive analytics has brought about a paradigm shift in how businesses approach CLV. AI-powered predictive models leverage machine learning algorithms to analyze vast amounts of data, uncover complex patterns, and make highly accurate CLV predictions. These models can dynamically adjust to changes in customer behavior, market conditions, and other external factors, providing businesses with a more precise and actionable understanding of their customer base. This article explores the transformative potential of AI in predictive CLV modeling, examining the various techniques and data sources that drive these advanced models. We will discuss the strategic benefits of AI-driven CLV, including personalized marketing, optimized customer segmentation, and enhanced customer retention strategies. Additionally, we will address the challenges associated with implementing AI-powered CLV models, such as data privacy concerns, integration with existing systems, and the interpretation of AI-generated insights.Through a detailed analysis of industry case studies, this article highlights the practical applications of AI-powered CLV models in maximizing long-term profits. We will also explore future trends in AI technology and their potential impact on CLV predictions, offering insights into how businesses can stay ahead of the curve in an increasingly competitive landscape. By the end of this article, readers will have a comprehensive understanding of how AI can revolutionize CLV predictions and drive sustained business growth.